Gene therapy for rare haematological and neurometabolic paediatric diseases - Vera Gallo; Alessandro Aiuti (Elsevier, 2024)
Nowadays, gene therapy hast the potential to cure an increasingly greater number of monogenic inherited disorders with absent or limited treatment options, and radically change their natural history. Hematopoietic stem cells (HSCs) represent one of the preferred targets for gene therapy, as genetic modification of multipotent cells ensures a permanent correction of the progeny. Gene-corrected HSCs and their progeny can also be used as cell vehicles to deliver molecules into the circulation and tissues, including the central nervous system or the skeleton. Major successes of this approach have been achieved in the field of monogenic blood disorders and neurometabolic diseases and several medicinal products have recently reached the stage of marketing approval by the EMA based on safety and efficacy data collected over more than 10 years of clinical trials. Gene therapy for these severe pathologies offers undeniable advantages over the sole alternative therapy of allogeneic transplantation because it can be applied to every patient, even when no matched HLA donor is available, reducing mortality and complications related to allogeneic transplantation, such as graft-versus-host disease, graft rejection, organ toxicity, and infections. Additionally, in neurometabolic diseases, gene therapy allows supra-physiological expression of the transgene, consequently producing supra-normal levels of the missing enzyme, providing a greater clinical benefit compared to allogeneic transplantation. Despite these remarkable achievements, several challenges remain for HSPC gene therapy regarding access to treatment and its sustainability for the future.